Pengaruh Keseimbangan Kehidupan Kerja Dan Beban Kerja Terhadap Kepuasan Kerja Karyawan Di PT Sinar Jaya Group Pada Unit Moda Transportasi Darat Area Bandar Udara Internasional Soekarno-Hatta - Anisa Saftari Situmeang; Widia Astuti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the partial and simultaneous influence between the influence of work-life balance and workload on employee job satisfaction at PT Sinar Jaya Group in the Land Transportation Mode Unit of Soekarno-Hatta International Airport Area . The method used in this study is quantitative with a descriptive associative approach and saturated sampling technique with a population and sample of 60 respondents. The value of the correlation coefficient results of work-life balance and workload on employee job satisfaction is at the level of 0.920, so the level of correlation between variables is interpreted as very strong. Simple linear regression of X 1 against Y, can be applied in the value of the regression equation, namely Y = 6.280 + 0.724 X 1. Hypothesis testing obtained the value of X 1 t count > t table or ( 8,410 > 2.001 ) and the value (sig) 0.000 < 0.05 thus shows that there is a positive and significant partial influence between work-life balance on employee job satisfaction at PT Sinar Jaya Group in the Land Transportation Mode Unit of Soekarno-Hatta International Airport Area . Simple linear regression of X 2 against Y can be applied in the regression equation value, namely Y = 3.121 + 0.906 X 2. Hypothesis testing obtained the value of X 2 t count > t table or ( 17,817 > 2.001 ) and a value (sig) of 0.000 < 0.05, thus indicating that there is a positive and significant partial influence between workload and employee job satisfaction at PT Sinar Jaya Group in the Land Transportation Mode Unit of Soekarno-Hatta International Airport Area . The results of this study are work-life balance (X 1 ) and workload (X 2 ) with the regression equation Y = 3.064 + 0.009X 1 + 0.899X 2 which can be interpreted as work-life balance and workload have a positive effect on job satisfaction . Partial or simultaneous hypothesis testing obtained f count > f table ( 156.022 > 3.16 ) and significant < 0.05 (0.000 < 0.05) then Ho3 is rejected and Ha3 is accepted, meaning work-life balance (X 1 ) and workload (X 2 ) have a positive and significant effect on job satisfaction. The results of the analysis of the Determination coefficient tested together have an influence of 0.846 or 84.6% while the remaining 15.4% is influenced by other factors.